Divine Violence, Law and Justice in Judaism from the Perspective of Walter Benjamin - Pažėraitė, Aušra Kristina (Religija ir kultūra, 2014)
This article deals with the question of divine violence according to Walter Benjamin, as being in opposition to mythical violence. Benjamin’s argumentation (among other examples) was based on references to biblical history and the law of Judaism, but was not sufficiently elaborated. How should we understand what Benjamin names “divine violence,” if we are not going into the field of political philosophy or theology, but remain in the religious one? How is it possible, and is it possible, to detect attitudes and ideas of religious Jewish tradition in the confrontation indicated by Benjamin? The article opts for a reading perspective, starting with the tradition of Orthodox Judaism, as it exists in rabbinical written and unwritten comments. In the process of analyzing the concept of divine violence in Orthodox Judaism, it was arrived at the conclusion that there is a whole complex of points connecting the rabbinical conceptions of divine law, justice and violence with Benjamin’s conception of divine violence. Even more, the last can be used to analyze the attitudes and rabbinic perspectives on law, which are based on dualistic controversies: between universalism and particularism (historicity, according to Derrida), and between the absolute nature of the Torah and earthly (historical, human) practices. These controversies are approached in the article by analyzing notions of “divine violence” (karet), the aspects of functionality of the rabbinical court concerning the problem of violence and the concepts of divine justice in Orthodox Judaism. This study leads to the conclusion that Benjamin’s notions are subtly reflecting the controversies that exist in rabbinical thinking and the concept of law.